KOMUNIKASI MANDOR TERHADAP KINERJA KARYAWAN PEMUPUKAN DI PT HANUSENTRA AGRO LESTARI - Wannur Qhalizah; Sri Ngapiyatun; Faradilla (Politeknik Pertanian Negeri Samarinda, 2022)
This research was motivated by several cases of communication processes that did not work well in palm oil companies. The foreman's lack of ability to direct his workers will lead to some of the conflicts that usually occur in oil palm plantations. Usually it starts with poor communication between the foreman and the employee, which allows both parties to disagree with the words that each party says. This study aims to analyze the foreman's communication on the performance of fertilization employees. The sampling method used the technique of distributing questionnaires to each foreman. The data is processed using the excel program. In addition, this study also uses a validity test to determine whether the contents of the questionnaire are valid or invalid and the data analysis is carried out in a qualitative descriptive manner. occurs, attitudes and views that occur in the fertilization foreman's communication. Based on the results of this study, the foreman's communication both verbal and non-verbal has a good impact on the performance of harvest employees in terms of arrival time, return time, application of fertilizer in the right place, on time, right type, right dose, right method and getting very good results.